2013
DOI: 10.1208/s12249-013-9945-1
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Interpolyelectrolyte Gastroretentive Matrix for the Site-Specific Zero-Order Delivery of Levodopa in Parkinson’s Disease

Abstract: Abstract. This study focused on developing a gastroretentive drug delivery system employing a triplemechanism interpolyelectrolyte complex (IPEC) matrix comprising high density, swelling, and bioadhesiveness for the enhanced site-specific zero-order delivery of levodopa in Parkinson's disease. An IPEC was synthesized and directly compressed into a levodopa-loaded matrix employing pharmaceutical technology and evaluated with respect to its physicochemical and physicomechanical properties and in vitro drug relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…For a cylindrical matric, if n = 0.45, the release mechanism is Fickian diffusion, nonFickian release or anomalous transport if 0.45<n<0.89, case II transport or zero-order release if n = 0.89, and super case II transport if >0.89 [19]. The release exponent n, for all the formulations except LBp displayed non-Fickian release or anomalous transport, indicating that the patterns of release from the matrices were a combination of release mechanisms other than diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…For a cylindrical matric, if n = 0.45, the release mechanism is Fickian diffusion, nonFickian release or anomalous transport if 0.45<n<0.89, case II transport or zero-order release if n = 0.89, and super case II transport if >0.89 [19]. The release exponent n, for all the formulations except LBp displayed non-Fickian release or anomalous transport, indicating that the patterns of release from the matrices were a combination of release mechanisms other than diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…Microbeads fabricated with a blend of alginate and irvingia gum significantly enhanced drug entrapment efficiency and controlled the release of diclofenac sodium over 7 h in comparison to microbeads fabricated with alginate alone [48]. Blends of natural and synthetic gums such as carboxymethyl cellulose/locust bean gum and methacrylate copolymer [49] to produce hydrogels have also been undertaken. Methacrylate copolymer is unsuitable for controlled release formulations, however, its interaction with carboxymethyl cellulose (CMC) produced a hydrogel thereby enhancing the mechanical strength of CMC.…”
Section: Polymer-polymer Blendingmentioning
confidence: 99%
“…Increase in concentration implies increase in molecular chains/bonds of the natural polymer available to interact with the mucus. The attachment/mucoadhesion of hakea gum to the mucus (mucin) may be based on non-covalent bondings such as Van der Waals, H-bonding and electrostatic interactions [49]. As the polymer hydrates in the presence of saliva, there is an increase in mobility of the polymer chains producing increased surface for adhesion/interactions with mucin.…”
Section: Natural Polymers For Controlled Releasementioning
confidence: 99%
“…It has been shown to exhibit synergistic interactions with other polysaccharides such as xanthan, k-carrageenan, guar gum, and karaya thereby modulating release mechanisms (24,25). It has also been previously demonstrated that a cationic methacrylate copolymer (Eudragit E100) interacts with sodium carboxymethylcellulose (NaCMC) to form an IPEC (26). NaCMC, a traditional hydrogel forming carbohydrate derivative, has a tendency to lose its shape in acidic medium exhibiting a first-order drug release profile.…”
Section: Introductionmentioning
confidence: 99%
“…Methacrylate copolymer such as Eudragit E100, mainly used as a film-coating agent, was observed to solubilize with ease in an acidic medium and so cannot be used for controlled release delivery. However, a series of studies undertaken in our laboratories indicated that the IPEC formed between the methacrylate copolymer and NaCMC has the potential to form a hydrogel maintaining its three-dimensional shape in acidic medium exhibiting a linear in vitro drug release over 24 h (26)(27)(28)(29). However, it underwent excessive swelling and bulk erosion.…”
Section: Introductionmentioning
confidence: 99%